2017
DOI: 10.1530/erc-17-0167
|View full text |Cite
|
Sign up to set email alerts
|

Differences in miRNA expression profiles between wild-type and mutated NIFTPs

Abstract: Noninvasive encapsulated follicular variants of papillary thyroid carcinomas have been recently reclassified as noninvasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTPs). NIFTPs exhibit a behavior that is very close to that of follicular adenomas but different from the infiltrative and invasive follicular variants of papillary thyroid carcinomas (FVPTCs). The importance of miRNAs to carcinogenesis has been reported in recent years. miRNAs seem to be promising diagnostic and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Molecular analysis cannot accurately differentiate these tumors because NIFTPs have molecular profiles similar to those of FA and IEFVPTC, with frequent RAS-like mutations [21][22][23]. However, recent studies have shown the miRNA expression profiles of NIFTPs to be different from those of other thyroid tumors [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis cannot accurately differentiate these tumors because NIFTPs have molecular profiles similar to those of FA and IEFVPTC, with frequent RAS-like mutations [21][22][23]. However, recent studies have shown the miRNA expression profiles of NIFTPs to be different from those of other thyroid tumors [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-193b-3p was found to be downregulated in the renal cortices from Cd-treated animals, and downregulation of this miRNA has been shown to promote autophagy and cell survival in mouse motor neuron-like cells [ 61 ]. Additionally, downregulated miR-342-3p expression is part of a shared dysregulated miRNA expression profile in both mutated non-invasive follicular thyroid neoplasms with papillary-like nuclear features (NIFTPs) and infiltrative and invasive follicular variants of papillary thyroid carcinomas (FVPTCs); and in contrast to wild type NIFTPs, this dysregulated miRNA expression profile is predicted to promote an invasive-like phenotype by altering cell adhesion and cell migration pathways [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression profiling of 798 miRNAs was carried out by the nCounter human v3 miRNA expression assay (NanoString Technologies, Seattle, WA, USA), as previously described [24].…”
Section: Methodsmentioning
confidence: 99%